Jumps in Oil Prices - Evidence and Implications - Marc Gronwald (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2009)
This paper studies the dynamic behavior of daily oil prices and finds strong evidenceof GARCH as well as conditional jump behavior. This implies that conditional heteroscedasticity is present and the empirical distribution of oil price changes has heavy tails. Thus, the oil price considerably sensitive to news and does not settle around a long-run trend. This finding has several important implications: First, this financial market variable-type behaviour hampers finding optimal depletion paths of oil as exhaustible resource as well as optimal decisions regarding the transmission to alternative technologies. Second, as the usage of oil is one of the main sources of carbon emissions, this non-existence of a clear long-run trend is likely to cause a current overextraction of oil, accompanied by severe consequences for the global climate.
Keywords: C22; Q30; 330; Oil price; conditional jumps; GARCH; Hotelling; climate change